DIGITAL WORKFLOW SYSTEMS IN EMERGENCY DEPARTMENTS: A SOCIO-TECHNICAL ANALYSIS OF STAFF EFFICIENCY AND WELL-BEING - Beata Szreder; Joanna Ślusarczyk; Piotr Pietrzyk; Natalia Stanek; Patrycja Krawczyk; Maja Łapaj; Aleksandra Jagiełło; Zuzanna Noweta; Milena Lewicka; Tamara Chodań (International Journal of Innovative Technologies in Social Science, 2026)
Background: The rapid digitization of healthcare has transformed the Emergency Department (ED) into a complex socio-technical system. While Digital Workflow Systems (DWS), including Electronic Health Records (EHR) and Clinical Decision Support Systems (CDSS), aim to optimize operational metrics, their impact on the cognitive ecosystem of healthcare professionals is often overlooked. This article conducts a socio-technical analysis of the dichotomy between IT-driven efficiency and staff well-being.Methods: Employing a hybrid systematic–narrative review approach underpinned by the SEIPS 2.0 framework, this study synthesizes literature published between 2018 and 2025. The analysis focuses on identifying how poorly designed interfaces contribute to systemic failures within the ED work system.Results: The findings reveal that interface design flaws significantly contribute to "technostress," cognitive overload, and moral injury among staff. The review identifies a "productivity paradox" where digital tools, intended to assist clinical workflows, instead become primary sources of professional burnout.Conclusion: To address these challenges, the paper proposes a framework for resilient, human-centric design. It emphasizes the critical need for integrating cognitive ergonomics and explainable AI into future ED information systems to ensure both patient safety and operator well-being.